2012
DOI: 10.1093/infdis/jis664
|View full text |Cite
|
Sign up to set email alerts
|

Heterovariant Cross-Reactive B-Cell Responses Induced by the 2009 Pandemic Influenza Virus A Subtype H1N1 Vaccine

Abstract: The A(H1N1)pdm09 vaccine induced production of PPAb with heterovariant reactivity, including antibodies targeting the conserved hemagglutinin stalk domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
2
22
0
1
Order By: Relevance
“…Recent studies demonstrated that infection or vaccination with the 2009 pH1N1 virus favors induction of broadly cross-reactive HA-specific Abs, including Abs reactive with the HA stalk (14)(15)(16)(17)(18). Importantly, our analysis adds to the limited available information on circulating levels of stalk-reactive Abs before and after pH1N1 exposure.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Recent studies demonstrated that infection or vaccination with the 2009 pH1N1 virus favors induction of broadly cross-reactive HA-specific Abs, including Abs reactive with the HA stalk (14)(15)(16)(17)(18). Importantly, our analysis adds to the limited available information on circulating levels of stalk-reactive Abs before and after pH1N1 exposure.…”
Section: Discussionmentioning
confidence: 87%
“…The amount of Ab secreted by an individual ASC is approximately the same in young and elderly subjects (31). There is evidence that ASCs induced by pH1N1 vaccination produce higher-affinity HA head-reactive Abs in older subjects (13,16), but this difference probably diminishes with affinity maturation of the response in the younger subjects. Overall, it is likely that the difference between age cohorts in the relationship between the ASC frequency and HAI fold increase primarily reflects a numerically greater ASC response to vaccination in the young cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exclusion is the pandemic virus H1N1pdm09: in that case, the generation of the cross-reactive antibodies directed to the subunit HA2 conservative sites after the disease and vaccination was shown [54,55].…”
Section: The Main Approaches To the Creation Of A Universal Vaccinementioning
confidence: 99%